DOI: 10.1007/978-3-540-85099-1_5
|View full text |Cite
|
Sign up to set email alerts
|

Consideration of Multiple Components of Emotions in Human-Technology Interaction

Abstract: Abstract. The study of users' emotional behavior as an important aspect of the user experience has been receiving increasing attention for the past few years. In this paper we discuss the multi-component character of emotions and its consideration in the area of human-technology interaction. Based on the approach proposed by Scherer [1], various aspects of emotions were investigated in an interactive context: subjective feelings, physiological activation, motor expression, cognitive appraisals, and behavioral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
14

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 22 publications
2
27
0
14
Order By: Relevance
“…Disputes arise between positions, such as there is a set of biologically hard-wired basic emotions (Izard, 2007), emotion is the result of a complex process of cognitive computation (Scherer, 2009), and conscious emotional experience is a conceptual and cultural reflection of a core physiological valence-arousal structure (Barrett, 2006;Russell, 1980). Many of these and other perspectives on what emotion is have been considered in human-technology interaction research (Lichtenstein et al, 2008;Mahlke and Minge, 2008), and it seems that it is too early for interaction researchers to side with a single psychological theory of emotion. In this article, appraisal theory is utilised (Scherer, 2009), but its use reflects its practical value in understanding emotional user experience as a process more so than an exclusive commitment to its meta-theoretical foundations.…”
Section: Introductionmentioning
confidence: 99%
“…Disputes arise between positions, such as there is a set of biologically hard-wired basic emotions (Izard, 2007), emotion is the result of a complex process of cognitive computation (Scherer, 2009), and conscious emotional experience is a conceptual and cultural reflection of a core physiological valence-arousal structure (Barrett, 2006;Russell, 1980). Many of these and other perspectives on what emotion is have been considered in human-technology interaction research (Lichtenstein et al, 2008;Mahlke and Minge, 2008), and it seems that it is too early for interaction researchers to side with a single psychological theory of emotion. In this article, appraisal theory is utilised (Scherer, 2009), but its use reflects its practical value in understanding emotional user experience as a process more so than an exclusive commitment to its meta-theoretical foundations.…”
Section: Introductionmentioning
confidence: 99%
“…A positive correlation between the arousal of Self-Assessment Manikin (SAM) and changes of SCR has already been identified in a study on mobile phone design (Mahlke and Minge, 2008). Though most of previous studies employed relatively high fidelity prototypes to see the emotional differences (perhaps it might come from colours and so forth), the present study used a low fidelity prototype, which has not been empirically demonstrated before.…”
Section: A Mixed Approach To Specify Emotion In Product Images: Cognimentioning
confidence: 78%
“…As emoções são complexas, difíceis de identificar e de mensurar; estão ligadas à reação de vários componentes que podem ser sintetizados em: avaliações cognitivas, sentimentos subjetivos, tendências comportamentais, reações fisiológicas e expressões motoras (SCHERER, 2005;MAHLKE;MINGE, 2008) e trazem à tona a discussão sobre o que as emoções são e o que precisa ser estudado quando se quer determinar o significado das mesmas (SCHERER, 2005). De maneira mais específica, o uso de imagens da face dos usuários para identificar as emoções permite uma interação pervasiva 1 .…”
Section: Contexto E Motivaçãounclassified
“…O indivíduo avalia constantemente o mundo ao seu redor e procura perceber as qualidades afetivas de eventos, objetos e recursos (FONTAINE et al, 2002); um processo complexo, dinâmico e com diversos aspectos (SCHERER, 2001;GONÇALVES et al, 2011;GONÇALVES et al, 2013b). Essa constante avaliação implica em utilizar recursos sensoriais, perceptivos e cognitivos, incluindo o pensamento racional, ou seja, uma mesma situação pode induzir diferentes emoções, dependendo da interpretação do usuário (SCHERER, 2005;MAHLKE;MINGE, 2008 Considerando os aspectos multidimensionais do espaço semântico (SCHERER, 2005), que será abordado na seção seguinte, o uso dessa abordagem faz sentido, pois considera a abrangência que a proposta reflete sobre os aspectos emocionais do indivíduo, a saber: (i) avaliações cognitivas; (ii) sentimentos subjetivos; (iii) tendências comportamentais; (iv) reações fisiológicas; e (v) expressões motoras (SCHERER, 2005;MAHLKE;MINGE, 2008;XAVIER;GARCIA;NERIS, 2012). Este trabalho considera aspectos emocionais relacionados as Expressões Motoras, mais especificamente as características da face do usuário.…”
Section: Teoria Componencial Das Emoçõesunclassified
See 1 more Smart Citation